Method of Approach to Application Stages and Procedures for Implementing Itchy Leaves Product - Eva Susanty Simaremare; Rosye Tanjung; Yuliana Ruth Yabansabra; Elsye Gunawan (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2019)
Depapre District is overgrown with itchy leaves which are useful as traditional medicines, for pain, fatigue, aches. This itchy leaf is widely available in the village and is used but has not been maximally managed. If itchy leaves are used, the economy of the community can be helped. The purpose of this activity is to implement the DPTM program which were to socialize, train, create, and evaluate the diversification of itchy leaf products. This activity also provided materials, supporting facilities and infrastructure in making itchy leaf products to the Depapre District community by involving the district government, the Indonesian Parliament and the BPOM as the relevant agencies. The method was carried out by means of coordination, implementation of activities in the form of lecture and lecture, practice of making itchy leaf products, and evaluation. This activity was carried out for 6 months. The conclusion obtained from this activity is that 51% of participants have participated in the same activity. As many as 98, 9% of participants benefited from this activity and 85% of the community were able to make itchy leaf products. There were three grinding technology units and three boxes of chemicals that are donated to the people of Depapre, each of which contains a device (stamper and mortar), materials (PEG 400, PEG 6000, methyl paraben, palm oil, talc, powder containers, labels, simplicia container, ointment container). In this activity also produced itchy leaf products in the form of simplicia and ointments.